Is the use of ICT in education leading to higher student outcomes? Analysis from the Spanish Autonomous Communities - Fernández-Gutiérrez, Marcos; Gimenez, Gregorio; Calero, Jorge (Computers and education, 2020)
The impact of ICT on educational achievements is a controversial issue which has attracted increasing attention from both policy makers and researchers. Policy makers have shown great enthusiasm over the positive impact of ICT on teaching and learning, investing substantially in this area. However, scientific evidence does not clearly support this effort. This paper analyses the impact of the use of ICT at school on students’ outcomes in compulsory secondary education in maths, reading and science. It uses data from three rounds of PISA (2009, 2012, 2015) for Spanish regions (Autonomous Communities). From this, the paper analyses whether, in those Autonomous Communities which have taken greater steps in increasing the use of ICT at school, educational outcomes have improved more than in the others. This analysis takes advantage of the availability of representative samples for Spanish Autonomous Communities in PISA, together with autonomy and variability across them as regards the use of ICT at school. This makes it possible to capture the effect of the different policies adopted by Spanish Autonomous Communities on the use of ICT at school. The results show that an increase in the use of ICT at school in an Autonomous Community does not render positive effects on PISA scores in maths and reading, whilst we do find a positive effect on PISA scores in science. These results suggest that the impact of ICT on educational outcomes depends on the subject and on the type of use of the technologies. As a result, policies oriented at increasing the educational use of ICT should require a careful evaluation, to identify in which fields, for which uses and for which methods of use, it may render a positive effect on educational outcomes. •Spanish regions have made substantial investments in equipping schools with ICT.•We evaluate whether regions that further increased ICT at schools achieved higher improvements in students' outcomes.•We estimate a multilevel model with data of 61,042 students, attending 2,195 schools, distributed in 13 regions.•A higher use of ICT at school has a positive effect on outcomes in science, but non-significant effects in maths and reading.